(untitled) (Revista Brasileira Multidisciplinar, 2024)
The search for sustainable solutions to ensure energy diversification and expand universal access for all is a priority for the Mozambican government. According to the bulletin of the National Institute of Statistics (INE), the basic indicators of Energy, Gas and Oil registered a considerable growth in electrical production, with greater emphasis on solar systems during the period from 2018 to 2021. exploratory research of the current stage of energy generation in the photovoltaic solar sector, presenting the installed generation capacities and prospects for sustainable development in Mozambique, based on the study of the Programa Energia para Todos implemented by the Government of Mozambique in cooperation with the Ministry of Mineral Resources and Energy (MIREME) with a view to promoting new policies for generation, efficient and inclusive supply by 2030. In order to contribute to this program, in the present study, detailed information was mapped regarding this model of electricity generation based on consultations with books, articles, periodicals, websites and reports. Among the results obtained, it is important to highlight some existing challenges that represent possible setbacks in encouraging the dissemination of solar energy in Mozambique, that is, the need for external funds and international donors constitutes a major barrier to investment in the construction of solar energy systems. distribution. However, this sector needs government assistance in the elaboration of new public policies for the promotion and financing directed at the operation, maintenance and manufacture of photovoltaic modules.